(untitled) (Salud, Arte y Cuidado, 2020)
In response to the need to implement curricular changes and generate contributions to the long-awaited university transformation in the UCLA Nursing Program, competency-based training is based on the theory of complex thinking, which considers the development of competencies as multiple processes of performance, in which the dimensions of knowledge are articulated, doing and being, necessary to solve a problem that emerges in a given social and professional context, considering that meaningful learning establishes that the articulation of these dimensions occurs consciously and reflexively in the student, while participating in the construction of his own knowledge and relates each new knowledge with the cognitive structures previously built by him, which gives meaning to the metacognitive process of raising awareness of the formation of the competent dimension to performance.